Analysis of Security Reality In Iraq for the period (1990 - 2014) - Shaker Jouda, Nidal; Abdulzahra, Suhayla (Opción, 2019)
The task of defense is one of the tasks practiced by human societies since an- cient times. This function has taken many forms and is in line with the social progress that culminated in the emergence of the state. This led to the forma- tion of armies, thus creating the so-called military establishment, which in turn has become a vital sector within the national economy. At the same time, the whole world is witnessing a major development in the increasing escala- tion of military spending in most countries of the world. The State seeks to achieve security and prosperity for its societies. In order to achieve this, some of them are linked their security to their military power, which cost them huge resources in the form of military expenditures which have reached a wide range. Of these countries is Iraq, where the military expenditures constituted an increasing economic burden on the public budget. The rise in military spending in Iraq because of the security conditions that passed three decades ago and more made it a state with heavy defense burdens in the world and that the search for its effects surrounded by many difficulties, most notably that the spending comes out often from the economic range to settle in the politi- cal sphere. This means that it is difficult to control. This spending has been a disincentive for investment and the country’s economic growth index has de- clined.so, it is necessary to diagnose the type of relationship between military expenditure and development effort variables and thus identify the real sourc- es of threat to security and try to remove them and divert resources away from military uses and to raise the indicators of sustainable development in Iraq